Effect of cholera toxin on the antiviral and anticellular activities of human leukocyte interferon. - Fuse, A (1979)
Cholera toxin added into cell cultures together with human leukocyte interferon inhibited the establishment of the antiviral state by interferon but not the anticellular activity of interferon in human cells. Sensitivities of various human cell lines to anticellular activities of interferon and cholera toxin were compared, but no direct correlation between both activities were demonstrated. These results suggest that antiviral and anticellular activities of interferon are due to different mechanism of actions, and cholera toxin does not act directly on the receptor site for interferon.